Xiaoyao Pills Ameliorate Depression-like Behaviors and Oxidative Stress Induced by Olfactory Bulbectomy in Rats via the Activation of the PIK3CA-AKT1-NFE2L2/BDNF Signaling Pathway - Ji, Yafei; Luo, Jie; Zeng, Jiuseng; Fang, Yang; Liu, Rong; Luan, Fei; Zeng, Nan (Frontiers in Pharmacology, 2021)
Numerous studies have revealed that oxidative stress is closely associated with the occurrence and development of depression. Xiaoyao Pills (XYW) are included in the Chinese Pharmacopoeia and are frequently used for treating anxiety and depression by smoothing the liver, strengthening the spleen, and nourishing the blood. However, the antidepressant effect of XYW have not yet been thoroughly investigated. The objective of our study was to investigate the antidepressant-like effects of XYW and the underlying molecular mechanism in the olfactory bulbectomized (OB) rat model of depression using the open field test (OFT), sucrose preference test (SPT), splash test (ST), and novelty suppressed feeding test (NSFT). Results showed that XYW (0.93 and 1.86 g·kg-1) significantly alleviated depression-like behaviors in rats, which was indicated by increased sucrose preference in the SPT, prolonged grooming time in the ST, decreased horizontal movement in the OFT, and shorter feeding latency in the NSFT. In addition, XYW treatment dramatically reversed the reduced activity of superoxide dismutase and the decreased level of glutathione, while also lowering levels of malondialdehyde, an inflammatory mediator (nitric oxide), and pro-inflammatory cytokines (interleukin-6 and 1β) in the serum and cortex of OB rats. Mechanistically, XYW induced marked upregulation of mRNA and protein expression levels of NFE2L2, KEAP1, GPX3, HMOX1, SOD1, NQO1, OGG1, PIK3CA, p-AKT1/AKT1, NTRK2, and BDNF, and downregulation of ROS in the cortex and hippocampus via the activation of the NFE2L2/KEAP1, PIK3CA/AKT1, and NTRK2/BDNF pathways. These findings suggest that XYW exert antidepressant-like effects in OB rats with depression-like symptoms, and these effects are mediated by the alleviation of oxidative stress and the enhancement of neuroprotective effects through the activation of the PIK3CA-AKT1-NFE2L2/BDNF signaling pathways.